Technical Debt in Practice: How to Find It and Fix It - Ernst, Neil; Kazman, Rick; Delange, Julien (Cambridge, Massachusetts: The MIT Press, 2021)
"A look at technical debt in software that focuses on the practical implications of technical debt for the entire software lifecycle"
Keywords: Computer software -- Development -- Quality control; Software failures -- Prevention; Project management; Maintainability (Engineering)